Reciprocity in spontaneous social behavior: Deepening our understanding of relational dynamics - Abrams, Jane; Mosri, Daniela Flores (Neuro-psychoanalysis (Madison, Conn.), 2024)
In this article, Testard et al. report on research, employing a novel method intended to create naturalistic conditions for identifying social behaviors, along with their neural signatures, in rhesus macaques. Rather than utilizing controlled experiments requiring the macaques to perform specific tasks, the design allowed subjects although caged, to engage in spontaneous interactions with other macaques. Using ethological analysis, computer vision, and wireless recording technologies, the authors reported findings that suggest broadly distributed coding of social behaviors in the cortex. The social interactions identified included affiliative, aggressive, locomotive, feeding, and grooming between males and females. Reciprocity in grooming was noted and grooming appeared to be calming when the macaques were faced with a threat. The authors suggest that reciprocity is central to building and maintaining strong social bonds that are protective under conditions of stress. Furthermore, their findings suggest that the cortical areas involved in these social behaviors may rely on subcortical regions, and they plan to explore this hypothesis in future research. This could be a possible bridge to Panksepp's contention that subcortical regions are associated with our social instincts and is a hypothesis of particular interest to neuropsychoanalysis.